Gravitational potential: determination and measurement at the points of the surface of a non-spherical inhomogeneous body - Karpenko, I.V. (Geofizicheskiy Zhurnal, 2011)
According to provisions of general theory of relativity gravity potential Ф of the point on the surface of heterogeneous body with a form close to ellipsoidal one in the first (after the newtonian) approximation Ф1 may be presented as a product Ф1=gR. Both values are measured instrumentally through the first and second derivatives of Ф and are the local characteristics of the point. And an acceleration accordingly for heterogeneous nonspherical body of a geoid type with a mass М looks like g=GM/R2.Authenticity of the first approximation is proved on the examples of solving some problems of the Earth physics. A possibility of direct measurement of gravity potential in the points of real surface of the Earth offers the challenge of solving many application dependent problems of energy state of separate areas of the Earth.